2013
DOI: 10.1192/bjp.bp.112.118422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the physical environment of psychiatric wards on the use of seclusion

Abstract: A number of design features had an effect on the use of seclusion and restraint. The study highlighted the need for a greater focus on the impact of the physical environment on patients, as, along with other interventions, this can reduce the need for seclusion and restraint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 32 publications
2
74
0
14
Order By: Relevance
“…In the same time, the sample increased from a selected population of eight hospitals in 2008, over a representative sample in 2010, to a near to nation-wide coverage in 2012 (Table 3). While the first 14 hospitals in 2008 and 2009 covered about 14,900 patients and 23,000 admissions (28), the findings gathered in 2012 covered 130,000 admissions and over 59,000 patients.…”
Section: Seclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same time, the sample increased from a selected population of eight hospitals in 2008, over a representative sample in 2010, to a near to nation-wide coverage in 2012 (Table 3). While the first 14 hospitals in 2008 and 2009 covered about 14,900 patients and 23,000 admissions (28), the findings gathered in 2012 covered 130,000 admissions and over 59,000 patients.…”
Section: Seclusionmentioning
confidence: 99%
“…More recently, in line with the English Psychiatric Intensive Care Units (PICU’s) a number of hospitals are developing intensive care as a specialization of Mental health care. Development of intensive care units not only aims at new building environments (28), but also at an increased professionalization of the care provided (52). In 19 psychiatric hospitals, a system of quality audits was set up to investigate the care provided.…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…Similar differences have been reported between different treatment wards [6]. This can be only partly explained by patient compilation [7] and the physical environment of the psychiatric wards [8]. Nurses have reported that the decision-making process for managing patients’ aggressive behavior poses inherent ethical dilemmas [9].…”
Section: Introductionmentioning
confidence: 66%
“…Visibility is a factor that has also been significantly associated with reduction in aggression and reduction in levels of seclusion on inpatient wards (Van der Schaaf, 2013). Changes in the EAI demonstrate that this increased with the new ward.…”
Section: Discussionmentioning
confidence: 97%
“…One study demonstrated that following a 50% reduction in bed numbers, although severe aggressive incidents to staff decreased, inter-patient violence actually increased (Palmstierna & Wistedt, 1995). Recently, a large multi-centred study, using seclusion as an outcome measure, showed that having more private space per patient, greater comfort and better visibility on the ward all contributed to a reduction in the need for restrictive measures on acute psychiatric units (Van der Schaaf et al 2013).…”
Section: Introductionmentioning
confidence: 98%